Hubungan Kualitas Kebugaran Jasmani Dan Kebiasaan Sarapan Pagi Dengan Prestasi Belajar Anak Sekolah Dasar SD Muhammadiyah 10 Tipes Surakarta - Nugrahani, Novita Rizky, Rustiningsih, SKM., M.Kes, Luluk Ria Rakhma, S.Gz., M.Gizi (2014)
Introduction: Quality of physical fitness and breakfast habit is one of the factors which affect learning achievement. Breakfast who are thing boring or thing that troublesome. Breakfast for school children aims to suffice energy needs during the move. Objective: The aims of study is to determine the relationship between the quality in of physical fitness and breakfast habits with learning achievement children grade Muhammadiyah 10 Tipes Surakarta elemantary school. Methods Research: That was used as methode in this study in addition observation with cross sectional. The population of this research is students grade V Muhammadiyah 10 Tipes Surakarta elementary school. The number of samples were 52 children who aged 10-12 year. Data quality physical fitness was obtained with run 1000 meters and the data the of breakfast habits abtained with food recall 24-hours during 7 days. The data using is analysed with statistical tPearson Product Moment test. Results: Result of research showed by that there one no relationship the quality of of physical fitness and learning achievement with significant value amounting to 0.797 (p = 0.797> 0,05). However there is a relationship breakfast habits and learning achievement, recording value amounting to 0.022 (p = 0.022 <0,05). Conclusion and Suggestions: There is no relationship quality of physical fitness with learning achievement and there is relationship breakfast habits with learning achievement children grade Muhammadiyah 10 Tipes Surakarta elemantary school .Increased the physical fitness and breakfast habits in order that the achievement of health good and the increasing learning achievement.